Analisis Peran Bank Syariah dalam Peningkatan Kemandirian Pengusaha Mikro dan Kecil - Edy, Sarwo (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2023)
This research analyzes the role of Islamic banks in enhancing the self-reliance of micro andsmall entrepreneurs (MSMEs). Through qualitative approach and in-depth interviews, thisstudy explores the contribution of Islamic banks in providing financial services that adhereto Sharia principles to MSMEs. Findings indicate that Islamic banks provide moreinclusive and sustainable financial access to MSMEs, facilitating business developmentand enhancing their self-reliance. However, challenges such as low understanding of Shariaproducts and limited access still hinder progress.